A century of science publishing : a collection of essays - Fredriksson, Einar H. (IOS Press, 2001)
Publishers of the science publishing scene comment on key developments throughout the 20th century. Some characteristic publishing enterprises, commercial and society owned, are described in a series of articles, followed by analysis of developments and possible changes to come.